The Boko Haram Insurgence In Nigeria Perspectives from Within - Anugwom, Edlyne Eze (New Directions in Islam, 2019)
This book focuses extensively on the Boko Haram insurgence in Nigeria. Providing deeper information on the origin and growth of the sect, it also examines antecedent and historical factors behind the insurgence, assessing a variety of socio-political drivers. The structure, organization and ideology of the sect are analysed, paying attention to internal splits within the group as well as external relations with the Nigerian state, and global jihadism. The diverse and wide ranging issues covered in the book makes it valuable for academic researchers, students and policy practitioners both within Africa and beyond. .